Keto-tarian : the (mostly) plant-based plan to burn fat, boost your energy, crush your cravings, and calm inflammation - Cole, Will (Functional medicine expert) (Avery, an imprint of Penguin Random House, 2018)
The keto craze is just getting warmed up. The ketogenic diet kick-starts your body's metabolism so it burns fat, instead of sugar, as its primary fuel. But most ketogenic plans are meat- and dairy-heavy, creating a host of other problems, especially for those who prefer plants at the center of the plate. Dr. Will Cole comes to the rescue with Ketotarian, which has all the fat-burning benefits without the antibiotics and hormones that are packed into most keto diets. First developed for individuals suffering from seizures, keto diets have been shown to reduce inflammation and lower the risk of many chronic health problems including Alzheimer's and some cancers. Adding a plant-based twist, Ketotarian includes more than 75 recipes that are vegetarian, vegan, or pescatarian, offering a range of delicious and healthy choices for achieving weight loss, renewed health, robust energy, and better brain function.